Analisis Persepsi dan Preferensi Konsumen Pada Kualitas, Kemasan, Varian Rasa dan Merek Produk Kerupuk Melarat di Desa Belendung Karawang - Ratna Deli Sari (Departement of Mathematics Education, 2023)
The cracker industry in Indonesia, particularly in the micro, small, and medium-sized enterprises (MSMEs) sector, holds significant potential. One prominent player in this industry is Kerupuk Melarat, a cracker producer based in Belendung Village, Karawang. Kerupuk Melarat offers a wide range of flavors and brands, each with distinct qualities and packaging options, catering to diverse consumer preferences. In the face of intensifying market competition, understanding consumer perceptions and preferences regarding the quality, packaging, flavor variants, and brands of Kerupuk Melarat is crucial for sustaining market relevance and competitiveness.This study aims to explore and analyze consumer perceptions and preferences concerning the aforementioned aspects of Kerupuk Melarat products in Belendung Village, Karawang. Employing a qualitative approach, the research delves into a comprehensive understanding of how consumers perceive and prioritize the quality, packaging, flavor variants, and brands of Kerupuk Melarat products.The findings of this study indicate that consumer perceptions and preferences towards Kerupuk Melarat in Belendung Village, Karawang are highly subjective and influenced by various factors, including personal experiences, individual preferences, and environmental influences. Factors such as brand image and past experiences play a significant role in shaping consumer perceptions and preferences. Moreover, consumer perceptions and preferences are also influenced by subjective factors like personal experiences, recommendations, and exposure to advertisements or promotional activities. Based on these insights, it can be concluded that consumers exhibit diverse preferences when it comes to flavor variants and brands of Kerupuk Melarat products in Belendung Village, Karawang. To enhance their brand image and appeal to target consumers, Kerupuk Melarat entrepreneurs are recommended to consider consumer perceptions and preferences. By aligning with consumer values, preferences, and expectations, producers can establish a robust brand image that resonates with their target market segment.